Assessment of physicochemical characteristics and hygienic practices along the value chain of raw fruit juice vended in Dar es Salaam City, Tanzania - Nonga, Hezron E.; Simforian, Edeltrud A.; Ndabikunze, Berbadette K. (Tanzania Journal of Health Research, 2014)
Fresh fruit juice is an essential component of human diet and there is considerable evidence of health and nutritional benefits. However, nature of the fruits used in juicing and unhygienic processes in the value chain may cause poor quality of juice. This cross-sectional study was conducted to assess physicochemical characteristics and hygienic practices along the value chain of raw fruit juice vended in Dar es Salaam, Tanzania. A total of 90 juice vendors were interviewed. Ninety juice samples were collected and analysed for physicochemical quality. The pH of juices ranged between 2.7 and 6.4, acidity 0.01% and 1.3% and, total soluble solids ranged between -1.5 and 18.04 ⁰Brix. Most juices (67.8%) had ⁰Brix levels below Codex recommended values classified as weak and watery. Juices were made of mango, passion, tamarind, sugar cane and mixture of these fruits sourced from open markets in the city. Water for washing of fruits and dilution of juices was from deep wells (53.3%) and taps (46.7%). About one third (37.8%) of the juice vendors didn’t wash the fruits before juicing and 44.4% didn’t boil water for juice dilution. Juice extraction was done by kitchen blenders, boiling in water and squeezing by simple machines. Juice pasteurization was not done. The majority of vendors (78.9%) stored juices in plastic buckets and juice was sold in glass cups, reused plastic bottles and disposable cups. Vending sites were restaurants, bus stands and along roadsides. The majority of premises (78.9%) were in unhygienic condition that likely encouraged or introduced contaminants to the juices. It is concluded that, the overall handling, preparation practices and physicochemical quality of raw fruit juices vended in Dare es Salaam City are poor. The government should educate the vendors on food safety and hygiene as well as enforcing regular monitoring of the quality of street fruit juices.